The Pengaruh Inflasi, PDRB, IPM dan Upah Minimum terhadap Tingkat Pengangguran Terbuka di Pulau Sumatera - Gresyavenita Saragih; Sunlip Wibisono; Zainuri Zainuri (Jurnal Ekuilibrium, 2023)
This study aims to determine the effect of inflation, Gross Regional Domestic Product (GDP), Human Development Index (IPM) and minimum wages on the Open Unemployment Rate on the island of Sumatra. This study uses secondary data in the form of panel data, with time series data from 2011 to 2020 and cross section data from 10 provinces on the island of Sumatra. Multiple linear model estimation analysis method with Fixed Effect Model (FEM) method. The results of the panel data estimation show that inflation has a negative and significant effect on the open unemployment rate, GDP has no effect on the open unemployment rate, HDI has a negative and significant effect on the open unemployment rate, and the minimum wage has a positive and insignificant effect on the open unemployment rate.